The influence of chronic anthropogenic disturbance and precipitation on endemic birds in a Seasonally Dry Tropical Forest. (March 2023) - Pereira, Iolanda M.S.; Azevedo Júnior, Severino M.; Oliveira, Fernanda M.P.; Santos, Lilia D'ark N.; Las-Casas, Flor Maria G.
Abstract: The current study investigated the effects of increase chronic anthropogenic disturbance (people pressure; grazing pressure and wood extraction), decreased precipitation, and the interaction of these factors on endemic bird species in the largest Seasonally Dry Tropical Forest found in South America, the Caatinga. The study was conducted in Catimbau National Park, Pernambuco, Brazil. We sampled endemic birds in 20 plots distributed across gradients of chronic anthropogenic disturbance and precipitation, through standardized censuses. We found isolated negative effects of people pressure and wood extraction on the richness and abundance of endemic birds. On the other hand, the number of species and individuals of birds were positively affected by the interactive effects of high precipitation levels and intense grazing. Species were affected and responded differently to the isolated and interactive effects of chronic anthropogenic disturbance predictors and precipitation. Our results demonstrated that different sources of chronic anthropogenic disturbances and decreases in precipitation regimes have pervasive effects on birds endemic to the Caatinga. In addition, they demonstrate the importance of well managed protected areas for the preservation and conservation of natural habitats and maintenance of biodiversity. Highlights: The interactive effect between increase grazing and precipitation results in greater richness and abundance of endemic birds. Increase wood extraction has a negative effect on the richness and abundance of endemic birds even in wetter areas. The chronic anthropogenic disturbance acted differently for each bird species.